Opioid Prescriptions by Specialty in Ohio, 2010–2014. Issue 5 (6th March 2017) - Weiner, Scott G; Baker, Olesya; Rodgers, Ann F; Garner, Chad; Nelson, Lewis S; Kreiner, Peter W; Schuur, Jeremiah D
Abstract: Background: The current US opioid epidemic is attributed to the large volume of prescribed opioids. This study analyzed the contribution of different medical specialties to overall opioids by evaluating the pill counts and morphine milligram equivalents (MMEs) of opioid prescriptions, stratified by provider specialty, and determined temporal trends. Methods: This was an analysis of the Ohio prescription drug monitoring program database, which captures scheduled medication prescriptions filled in the state as well as prescriber specialty. We extracted prescriptions for pill versions of opioids written in the calendar years 2010 to 2014. The main outcomes were the number of filled prescriptions, pill counts, MMEs, and extended-released opioids written by physicians in each specialty, and annual prescribing trends. Results: There were 56, 873, 719 prescriptions for the studied opioids dispensed, for which 41, 959, 581 (73.8%) had prescriber specialty type available. Mean number of pills per prescription and MMEs were highest for physical medicine/rehabilitation (PM&R; 91.2 pills, 1, 532 mg, N = 1, 680, 579), anesthesiology/pain (89.3 pills, 1, 484 mg, N = 3, 261, 449), hematology/oncology (88.2 pills, 1, 534 mg, N = 516, 596), and neurology (84.4 pills, 1, 230 mg, N = 573, 389). Family medicine (21.8%) and internal medicine (17.6%) wrote the most opioid prescriptions overall. Time trends in the average number of pills and MMEs per prescription also varied depending on specialty. Conclusions: The numbers of pills and MMEs per opioid prescription vary markedly by prescriber specialty, as do trends in prescribing characteristics. Pill count and MME values define each specialty's contribution to overall opioid prescribing more accurately than the number of prescriptions alone.